Pattern of Antidepressant Utilization and Cost in Iran from 2006 to 2013 in Comparison with Other Countries - Fatemeh Soleymani; Forouzan Taheri; Elizabeth Roughead; Shekoufeh Nikfar; Mohammad Abdollahi (Springer, 2018)
Antidepressant prescribing patterns have changed globally over the past few years, with conventional drugs including tricyclic antidepressants and monoamine oxidase inhibitors being replaced by selective serotonin reuptake inhibitors (SSRIs) and novel antidepressants. The objective of this study was to assess antidepressant utilization in Iran from 2006 to 2013 and to show Iran's situation in antidepressant consumption compared with other countries. A cross-sectional study was undertaken using prescription claims data from Iranian insurance agencies. In addition, total antidepressant sales data were obtained from the databank of the national regulatory authority. Medicines were classified according to the Anatomic Therapeutic Chemical (ATC2012 edition) System. The Organisation for Economic Co-operation and Development data were used to compare national results from Iran with other countries. Antidepressant sales were four-fold higher than those of prescribed antidepressants [24 defined daily doses (DDD)/1000 inhabitants/day were sold whereas 6 DDD/1000 inhabitants/day were prescribed in 2013]. The trend in antidepressant prescriptions and consumption showed increasing use of SSRIs (N06AB). Nortriptyline, fluoxetine, and citalopram accounted for more than 60% of all prescriptions each year. The type of adverse reactions with new expensive antidepressants may seem convincing for the growing tendency toward using these medicines, but considering their high costs, health policymakers have to be aware of the risk of overprescription of newer antidepressant. Drivers of over-the-counter purchase of antidepressants need to be explored.